Refusing to Hyphenate: Doukhobor Autobiographical Discourse - Rak, Julie (My University, 1998)
My thesis, Refusing to Hyphenate: Doukhobor Autobiographical Discourse brings together recent theories of autobiography with a consideration of alternative autobiographical writing and speaking made by a Russian-speaking migrant group, the Doukhobors of Canada. The situation of the Doukhobors is ideal for a consideration of alternate autobiographical forms, since Doukhobors have fallen outside liberal democratic discourses of Canadian nationalism, land use and religion ever since their arrival in Canada in 1899. They have turned to alternate strategies to retell their own histories against the grain of the sensationalist image of Doukhobors propagated by government commissions and by the Canadian media. My study is the first to recover archived autobiographical material by Doukhobors for analysis. It also breaks new ground by linking new developments in autobiography theory with other developments in diaspora theory, orality and literacy and theories of performativity, as well as criticism that takes issues about identity and its relationship to power into account.
When they had to partially assimilate by the 1950s, some Doukhobors made autobiographical writings, translations and recordings that included interviews, older autobiographical accounts and oral histories about their identity as a migratory, persecuted people who resist State control. Others recorded their protests against the British Columbian government from the 1930s to the 1960s in collective prison diaries and legal documents. My selections from these writings, interviews and recordings indicate how some Doukhobors use aspects, but not immediately recognizable forms, of autobiographical discourse to engage dominant ideas about nation, property, literacy and bourgeois citizenship which have threatened to erase Doukhobor communities. These strategies combine aspects of "classic" autobiography and Doukhobor ways to remember and recollect which reclaim Doukhobor identities as plural and situated in a Canadian context, but not connected to Canadian identity by a hyphen that keeps Doukhobors forever separate.
Keywords: English Language and Literature; English Language and Literature